Ocular Manifestations of Acute Secondary Angle Closure Associated With Lens Subluxation - Jing, Qinghe; Chen, Tianhui; Chen, Zexu; Lan, Lina; Zhao, Chen; Jiang, Yongxiang (Frontiers in Medicine, 2022)
Purpose: To evaluate the clinical characteristics and ocular features of patients with acute secondary angle closure, associated with lens subluxation (ASAC-LS). Methods: We performed a retrospective study at the EENT Hospital of Fudan University. A total of 41 affected eyes, from 41 patients, were enrolled in this study. 20 affected eyes were part of the ASAC-LS cohort and 21 affected eyes were included in the acute primary angle closure (APAC) cohort. The best-corrected visual acuity (BCVA), intraocular pressure (IOP), axial length (AL), minimum corneal curvature (K1), maximum corneal curvature (K2), and anterior chamber depth (ACD) were measured and compared between the 2 cohorts. Inter-eye (intraindividual) comparison was also performed. Results: The ASAC-LS cohort exhibited younger ages, more frequent trauma history (35%), lower IOP (27.43±13.86 mmHg vs. 41.27±10.36 mmHg), longer AL (23.96±2.60 mm vs. 22.49±0.77 mm), shallower ACD (1.28±0.38 mm vs. 1.58±0.23 mm), and bigger ACD differences (0.99±0.52 mm vs. 0.15±0.19 mm), as compared to the APAC cohort (all p<0.05). Moreover, eyes from the lens subluxation cohort experienced worse BCVA, higher IOP, and shallower ACD than their matched unaffected eyes (all p<0.05). Although longer AL, shallower ACD, and bigger ACD differences were strongly correlated with lens subluxation in univariate logistic regression analysis, only the ACD difference remained significant in the multivariate model (p=0.004, OR=1510.50). Additionally, according to the ROC curve analysis, both ACD and ACD differences had greater value in differential diagnosis of ASAC-LS and APAC, with a cut-off value of 1.4mm and 0.63mm, respectively. Conclusions: Shallower ACD and larger ACD differences provide promising diagnostic potential for patients with acute secondary angle closure, associated with lens subluxation.